2017
DOI: 10.18388/abp.2017_2205
|View full text |Cite
|
Sign up to set email alerts
|

Acute tadalafil administration increases plasma fatty acids without changes in the inflammatory response in healthy men

Abstract: Tadalafil, in human subjects, increases lipolysis as evidenced by a significant increase in circulating FFAs and glycerol, without affecting the plasma cGMP and NO levels; noticeably, the increase in FFAs did not develop an inflammatory response. Further well-controlled studies are warranted to assess the impact of tadalafil administration on weight/fat loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Recently, our laboratory, along with others, has demonstrated that PDE5i, including tadalafil, may modulate muscle metabolism and response to ROS under physiological and pathological conditions, in either in vitro or in vivo studies [ 27 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our laboratory, along with others, has demonstrated that PDE5i, including tadalafil, may modulate muscle metabolism and response to ROS under physiological and pathological conditions, in either in vitro or in vivo studies [ 27 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of IGF-I and IGF-II were determined using the Bio-Plex Suspension Array System (Bio-Rad Laboratories Hercules, California USA) ( 29 ). The intra-assay and inter-assay coefficients of variation of the hormones evaluated were 2% and 6% for IGF-I and 2% and 4% for IGF-II, respectively.…”
Section: Methodsmentioning
confidence: 99%